Peptídeos miméticos de antígenos de Strongyloides venezuelensis como nova ferramenta no diagnóstico da estrongiloidíase humana e no desenvolvimento de vacinas em modelo experimental - Sousa, José Eduardo Neto de (2018)
Strongyloidiasis is a chronic human parasitic infection caused by Strongyloides stercoralis and presents a wide geographical distribution with predominance in tropical and subtropical areas. The diagnosis is difficult by due to intermittent elimination of larvae in the faeces and the large number of asymptomatic individuals. Thus, detection of serum immune complexes in patients with strongyloidiasis may be a strategy to detect early active infection in patients with strongyloidiasis. The diagnosis of infected persons and the development of vaccines would be an excellent strategy of public health, favoring the breakdown of the biological cycle of the parasite. The aim of this study was to use phage display technology to select clones of phages binding the synthetic peptide C10, application of these ligands in the detection of immunocomplexes in sera of patients with human strongyloidiasis and to verify the use of mimetic peptides of S. venezuelensis antigens in vaccine formulations in the control of experimental strongyloidiasis. The selection of clones binding to C10 was performed by phage display, later the phages were titrated, and their DNA sequenced. C4 and G8 clones were selected and used in detection immune complexes by enzyme-linked immunosorbent assays (ELISA) in serum samples from patients with strongyloidiasis and in the detection of S. venezuelensis antigens by ELISA and indirect immunofluorescence (IFAT). To evaluate vaccine potential, two immunizations were performed at 15-days intervals each, followed by a challenge infection with S. venezuelensis infective larvae (15 days after the last immunization). For animal’s immunization were used the clones C9 and C10 and wild phage M13. Two types of aluminum hydroxide (alum) and saponin adjuvants were used. Serum titers were performed throughout the experiment to monitor seroconversion of IgG titers. Egg count per gram of faeces (EPG) was performed during the 21 days of infection. The clones C4 and G8 more reactive to the C10 peptide. The C4 phage presented the highest diagnostic performance: sensitivity of 83%, specificity of 89% with AUC of 0.953 and Youden index 0.713. When comparing the 8th day results of the animals immunized with alum and clones C9, C10 and the combination of both (C9 and C10), it was observed that the egg reduction rates in the faeces were 50, 50 and 78%, respectively, while the rats immunized with saponin adjuvant the reduction was 59, 55 and 80%, respectively. The groups immunized with the combination of C9 + C10 (alum and saponin) showed greater reduction of EPG. In conclusion, the phage display technique was effective in selecting specific clones of the C10 peptide. Anti-C10 phages can detect immune complexes in serum samples from patients with strongyloidiasis with reasonable sensitivity and specificity. Clones C4 and G8 recognize S. venezuelensis antigens. Immunization with phage expressing both C9 and C10 peptide with both adjuvants was effective in reducing the S. venezuelensis EPG. Mimetic peptides of S. venezuelensis can be used as a new tool in the serological diagnosis of human strongyloidiasis and in the development of vaccines in an experimental model.